IGNITE integrating media architecture and modulable design into an esports hub in Cebu City for the creative industry - Teves, Troy Edgar F. (College of Architecture, University of the Philippines Diliman, 2023)
The esports scene has over the years seen a significant rise in revenue and viewership internationally and locally. However in the country, the esports scene is in a nascent stage and has yet to reach its full potential compared to its Southeast Asian neighbors, due to the lack of government initiative and facility support over the years despite the large audience and accolades of Filipino players and organizations. With recent laws and programs in the creative industry to help post-pandemic recovery, an opportunity to develop the local esports scene and establish its identity is given. This project aims to answer how an esports hub, through a comprehensive design, can help transcend and ignite the nascent esports scene. Integration of media architecture, a recent concept in the field that blends portrayal of visual arts into the architectural design, is implemented to capitalize the visual and adaptive nature of esports and gaming as well as for advertising. Modulable design is also integrated to provide multipurpose use to the arena for other creative industries as well as for sustainability. Cebu City would be a prime location for the project, as both a prominent tourist destination and for the gaming scene it has developed through local initiatives and foreign interest. The establishment of Ignite: Esports Hub addresses the potential of developing our esports identity through a design purpose-built for the industry that can help foster the growth of competitors and viewers alike. In conclusion, our esports scene is one that requires investment and commitment, and an architectural design with a focus on esports is a way to healthily move forward the esports scene and go beyond its current form to become a contender not only in our region but internationally.